Comparative viscometric study of pure and acetylated gum Arabic using different plot methods - S.I, Alhassan; S.Y, Sule; R., Murtala; H.I, Rasheed; A.A, Baso; F.A, Sheshe; S.C, Jafar (International Journal of Advanced Chemistry, 2020)
Acetylation of gum Arabic was achieved using acetic anhydride as solvent. The ester group formed was confirmed by FTIR spectra having absorption band of 750 cm-1 â€“ 700 cm-1. Viscometric study of the pure and acetylated samples was carried out. Relative viscosity of acetylated gum was found to be higher than that of the pure gum. Intrinsic viscosity was determined for the two samples using different plot methods taking Hugginâ€™s plot as standard. The intrinsic viscosity was found to be 86.43 cm3/g and 64.59 cm3/g for acetylated and pure gum arabic respectively. Relative errors of other methods for the two samples was compared to that of Huggins and the plots that are most comparable to Huggins with relative errors less than 5% are; Martin, Lyon-Tobolsky, Staudinger-Heuer, Maron-Reznik and our proposed method. The proposed method which was a modification of the Kreiser method gave relative error less than 2 %, for both pure and modified gum. Whereas the Kreiser method gave relative error greater than 15 % for both methods. The critical concentration for the samples was found to be 0.0116 g/cm3 and 0.0155 g/cm3 for acetylated and pure gum respectively. This shows that there was no molecule-molecule entanglements during viscosity measurements.Â